Transfer Pricing and Digital Taxation in North America: Policy Divergences and Impacts - Navarro, Jorge (MZ Journal of Artificial Intelligence, 2024)
In recent years, transfer pricing and digital taxation have emerged as critical issues for governments and multinational corporations in North America. This paper explores the complexities of transfer pricing regulations and the rise of digital taxation, highlighting policy divergences across the region. It examines how differing approaches to these issues impact businesses, tax revenues, and the overall economy. The study underscores the necessity for harmonization in tax policies to address the challenges posed by globalization and digitalization. By analyzing existing frameworks and proposing potential solutions, this research aims to contribute to the ongoing discourse on equitable tax practices in the digital age.